Physiological Events in Clostridium acetobutylicum during the Shift from Acidogenesis to Solventogenesis in Continuous Culture and Presentation of a Model for Shift Induction - Helga Grupe; Gerhard Gottschalk (1992)
The pH of continuous cultures of Clostridium acetobutylicum growing at pH 5.6 was allowed to decrease to 4.3 after acid production and thereby to shift the cultures from acetate and butyrate to acetone and butanol formation. Several parameters were determined during the shift. An increase in the intracellular acid concentration to 440 mM was recorded. An excess of undissociated butyric acid but not of acetic acid just before the shift to solventogenesis was followed by a decline in acid production and subsequently by the uptake of acids. The intracellular ATP concentration reached a minimum before the onset of solventogenesis; this presumably reflects the ATP-consuming proton extrusion connected with the increase in the ΔpH from 0.7 to 1.4 units. The pool of NADH plus NADPH exhibited a drastic increase until solventogenesis was induced. The changes in the ATP and ADP and NADH plus NADPH pools during these pH shift experiments were the beginning of a stable metabolic oscillation which could also be recorded as an oscillation of the culture redox potential under steady-state solventogenic conditions. Similar changes were observed when the shift was induced by the addition of butyrate and acetate (50 mM each) to the continuous culture. However, when methyl viologen was added, important differences were found: ATP levels did not reach a minimum, acetoacetate decarboxylase activity could not be measured, and butanol but not acetone was produced. A model for the shift is proposed; it assumes the generation of two signals, one by the changed ATP and ADP levels and the other by the increased NAD(P)H level.